Finger Family Collection YouTube Videos Nursery Rhymes Impact on Iraqi EFL Pupils' Performance in Speaking Skills - Hussein Al-Mosawi, Fatima Rahim Abdul (Opción, 2019)
This study aims at finding out finger family collection YouTube videos nursery rhymes impact on Iraqi EFL Pupils' Performance in speaking skills. To achieve the aims of the study, null hypotheses have been put on after being subjected to experiment. The results show that there is no a significant statistical difference between the mean scores of the development of the experimental group taught by finger family collations YouTube videos. In conclusion, Family Finger can be considered as an activity style in teaching English for third Primary pupils, because of the positive effect on the development of English language skills.